Purinergic signaling in inflammatory renal disease - Arulkumaran, Nishkantha; Turner, Clare; Sixma, Marije; Singer, Mervyn; Unwin, Robert J.; Tam, Frederick W. (Frontiers in Physiology, 2013)
Extracellular purines have a role in renal physiology and adaption to inflammation. However, inflammatory renal disease may be mediated by extracellular purines, resulting in renal injury. The role of purinergic signalling is dependent on the concentrations of extracellular purines. Low basal levels of purines are important in normal homeostasis and growth. Concentrations of extracellular purines are significantly elevated during inflammation and mediate either an adaptive role or propagate local inflammation. Adenosine signalling mediates alterations in regional renal blood flow by regulation of the renal microcirculation, tubulo-glomerular feedback, and tubular transport of sodium and water. Increased extracellular ATP and renal P2 receptor-mediated inflammation are associated with various renal diseases, including hypertension, diabetic nephropathy, and glomerulonephritis. Experimental data suggests P2 receptor deficiency or receptor antagonism is associated with amelioration of antibody-mediated nephritis, suggesting a pathogenic (rather than adaptive) role of purinergic signalling. We discuss the role of extracellular nucleotides in adaptation to ischaemic renal injury and in the pathogenesis of inflammatory renal disease.